Failed by the System: A Content Analysis of Midwives’ Experiences and Challenges When Providing Termination of Pregnancy Care - Armour, S; Keedle, H; Gilkison, A; Dahlen, HG (Wiley, 2025)
Aim: To explore the experiences of midwives' when caring for women undergoing pregnancy termination after 14 weeks in Australia and New Zealand and the challenges they encounter. Design and Methods: Content analysis was used to analyse 1389 responses to 10 open text questions embedded in a web-based cross-sectional survey. Current understandings of grief and stigma were applied to the data. The SRQR guideline was used for reporting. Results: Data were grouped into four main categories: ‘Failed by the system’, ‘Emotionally and morally challenged’, ‘Midwifery at the core’ and ‘Caring for myself’. Midwives strongly supported women's reproductive health choices and described delivering compassionate, woman-centred care during pregnancy termination. Midwives reported receiving minimal pre-registration education. Grief and sadness were prevalent emotions. Midwives described witnessing and experiencing abortion stigma. Other challenges that affected midwives' experiences included a lack of emotional and practical support. Self-care strategies did not provide enough relief to midwives to overcome the emotional impact of providing care. Conclusion: Midwives believe they deliver the very best of midwifery care to women who undergo pregnancy termination after 14 weeks but are affected by significant grief. Midwives not only witness stigma but also experience this as care providers. Failed by the healthcare systems that employ them, they lack appropriate support to overcome the emotional and moral challenges they encounter. Patient or Public Contribution: No patient or public involvement.
Keywords: 4204 Midwifery; 4205 Nursing; 42 Health Sciences; Contraception/Reproduction; 8.1 Organisation and delivery of services; 7.1 Individual care needs; 7.3 Management and decision making; Generic health relevance; Reproductive health and childbirth; 3 Good Health and Well Being; 1110 Nursing; 1117 Public Health and Health Services; 1701 Psychology; Nursing; 4203 Health services and systems; 4205 Nursing; Humans; Female; Pregnancy; Australia; New Zealand; Cross-Sectional Studies; Nurse Midwives; Adult; Abortion, Induced; Midwifery; Middle Aged; Surveys and Questionnaires; Grief; Humans; Female; Pregnancy; Australia; New Zealand; Cross-Sectional Studies; Nurse Midwives; Adult; Abortion, Induced; Midwifery; Middle Aged; Surveys and Questionnaires; Grief